Controlled vocabularies in scientific literature’s indexing: The case of the 1918 pandemic - Garcia Alsina, Montserrat; Cobarsi-Morales, Josep (Advanced Notes in Information Science, 2024)
The scientific interest in the 1918 flu pandemic has been reinforced by the emergence in the early 21st century of epidemic pneumonia diseases caused by a virus, and more recently, the emergence of the SARS-CoV-2 virus, which caused the global pandemic known as “COVID-19,” in 2020. This paper presents the findings of an exploratory study on the use of controlled languages in the scientific community, with the aim of identifying the knowledge generated and needed. This research has two objectives. The first is to identify the relevant controlled languages used by the scientific community to label the knowledge produced. The second is to ascertain the role played by controlled vocabularies in the recovery of scientific production. The research is centered on the production of literature concerning the 1918 pandemic, which has been indexed in two widely utilized databases: Web of Science and Scopus. Additionally, the investigation encompasses the controlled vocabularies pertinent to medical and health sciences subjects. Following the identification of articles pertaining to the subject matter, the scientific journals from which the articles have been retrieved are selected. Subsequently, the paper examines the instructions and guidance provided to authors by the journals in question, with the objective of analyzing the role played by keywords and controlled vocabularies in the scientific literature with regard to indexing and recovering knowledge in scientific databases. The preliminary results indicate that controlled vocabularies are infrequently utilized by journal publishers, as they are not included in the instructions provided to authors.